2022
DOI: 10.31234/osf.io/es89d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gendered Perceptions of East and South Asian Men

Abstract: Gendered race theories argued that Asian male faces are perceived to be more feminine and less masculine than other racial groups like Black male faces, but extant research focused exclusively on East Asian men while overlooking South Asian men. Four studies (N = 1,329) examined the perceived masculinity and femininity of East and South Asian men and women using facial photographs. We consistently found that East Asian men were perceived to be more feminine and less masculine compared to South Asian, White, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Second, the "race is gendered" effect was replicated only in the contrast between Asian men and Black men, but not between Asian women and Black women. This gender nuance in racial stereotypes is consistent with recent findings (Goh & Trofimchuk, 2022) and may help explain why Asian men (but not women) are stereotyped as less moral/trustworthy, which is likely related to their lower prototypicality (Schug et al, 2015). Overall, this research reveals how English speakers naturally expressed intersectional stereotypes about Asian and Black men and women in the real world.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Second, the "race is gendered" effect was replicated only in the contrast between Asian men and Black men, but not between Asian women and Black women. This gender nuance in racial stereotypes is consistent with recent findings (Goh & Trofimchuk, 2022) and may help explain why Asian men (but not women) are stereotyped as less moral/trustworthy, which is likely related to their lower prototypicality (Schug et al, 2015). Overall, this research reveals how English speakers naturally expressed intersectional stereotypes about Asian and Black men and women in the real world.…”
Section: Discussionsupporting
confidence: 87%
“…One recent study found a perceiver difference that Asian men and Black women (i.e., counter-stereotypical groups) held weaker race-gender associations, while Chinese (vs. American) participants held stronger race-gender associations (Axt et al, 2023). Another recent study identified a target difference that East Asian men (but not women) were viewed as less masculine and more feminine, compared to their South Asian, White, and Black counterparts (Goh & Trofimchuk, 2022).…”
Section: The Gendered Race View Of Asian and Black Stereotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Black and White wrestlers’ capabilities could appear differently to perceivers based on concomitant stereotypes. Additionally, the history of Asian wrestlers adopting underhanded foreign heel characters in the United States (e.g., Japanese wrestler Yoshihiro Tajiri using the “Asian mist”) could undermine an interest in booking Asian men as top stars for not appearing sufficiently masculine by American standards (Goh & Trofimchuk, 2022; Johnson et al, 2012). Nonetheless, Japanese wrestling promotions present Asian wrestlers as rugged (e.g., Kenta Kobashi and Tomohiro Ishii), suggesting many stereotypes are Western-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the historic employment of Asian wrestlers to adopt underhanded foreign heel characters in U.S. (e.g., Yoshihiro Tajiri using the "Asian mist") could undermine an interest in booking Asian men as top stars for not appearing sufficiently masculine by American standards (Goh & Trofimchuk, 2022;Johnson et al, 2012). Nonetheless, Japanese wrestling promotions present many Asian wrestlers as rugged characters (e.g., Kenta Kobashi, Tomohiro Ishii), suggesting these stereotypes are Western-specific.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%